2019
DOI: 10.3390/ijms20020351
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Health Effects on Cardiovascular and Neurodegenerative Disorders: A Review and Meta-Analysis

Abstract: Several studies have demonstrated that polyphenol-enriched diets may have beneficial effects against the development of degenerative diseases, including atherosclerosis and disorders affecting the central nervous system. This activity has been associated not only with antioxidant and anti-inflammatory properties, but also with additional mechanisms, such as the modulation of lipid metabolism and gut microbiota function. However, long-term studies on humans provided controversial results, making the prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 102 publications
3
127
0
1
Order By: Relevance
“…Therefore, with the advances in microbiota sequencing techniques, studies of polyphenols should pay particular attention to the population of the gut microbiota in the experimental model. Also, there are many differences found between different studies, in terms of formulation, dose, source, and identity of the polyphenol under investigation, which should be taken into account very carefully (Potì, Santi, Spaggiari, Zimetti, & Zanotti, ). Consensus in the source and dose of polyphenol should be considered in future studies.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, with the advances in microbiota sequencing techniques, studies of polyphenols should pay particular attention to the population of the gut microbiota in the experimental model. Also, there are many differences found between different studies, in terms of formulation, dose, source, and identity of the polyphenol under investigation, which should be taken into account very carefully (Potì, Santi, Spaggiari, Zimetti, & Zanotti, ). Consensus in the source and dose of polyphenol should be considered in future studies.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Zanotti, 2019). Consensus in the source and dose of polyphenol should be considered in future studies.…”
mentioning
confidence: 99%
“…These benefits are largely attributed to the high content of phenolic compounds in bilberry and lingonberry, compounds that are recognized to have multiple biological activities. In many research papers, it was shown that the antioxidant activity of phenolic compounds is correlated with their health benefits [51][52][53]. Regarding this approach of action of polyphenols as antioxidants in humans, Dangles [3] clarified very well that the cardioprotective effects of phenolic compounds involve their anti-inflammatory rather than their antioxidant properties.…”
Section: Potential Pharmaceutical and Biological Activity Of Phenolicmentioning
confidence: 99%
“…Data describing the effect of HCAs on the gut microbiota are scarce compared to other classes of phenolics, e.g. anthocyanins . Therefore, a summary of recent studies (pre‐clinical and clinical) and the effect of HCAs on gut microbiota is given below.…”
Section: Hca Interactions With the Gut Microbiotamentioning
confidence: 99%
“…anthocyanins. [236][237][238][239][240] Therefore, a summary of recent studies (pre-clinical and clinical) and the effect of HCAs on gut microbiota is given below.…”
Section: Caffeic Acid: Recent Advancesmentioning
confidence: 99%